E-portfolio readiness among pre-service teachers and practicum supervisors at a Malaysian university - Wirawati Ngui Yi Xe; Tan Choon Keong; Eugenia Ida Edward (ResearchGate, 2023)
Innovative practices in teacher education programmes produce a ripple effect in the types of teaching and learning methods that will be practiced in the classroom. In line with the prevalent use of technology for education, electronic portfolios (e-Portfolios) have been introduced across higher education institutions. This study aimed to explore learner and supervisor readiness prior to the implementation of an e-Portfolio in a teacher education programme. The e-Portfolio is intended to be used for professional development during practicum by pre-service teachers who major in Teaching English as a Second Language (TESL) at a Malaysian public university. This is a qualitative study that involved data collection through semistructured interviews with 8 undergraduate students and 4 lecturers. The data were transferred to NVivo 12 and thematic analysis was employed to analyse the data. Based on the Technology Readiness construct, the motivators and inhibitors in relation to the e-Portfolio were revealed. Motivators pertaining to the e-Portfolio comprised communication and shareability, accessibility and convenience, and tracking progress and documenting performance. On the other hand, the inhibitors included learning to use the ePortfolio and workload. The findings of this study revealed pertinent issues that need to be considered prior to introducing innovative tools in teacher education programmes.